The impact of educational software on student learning and academic achievement: Evidence from Jordan - Almubasher, Zakaria Mahmoud; Abu-Rahme, Mohammed O; Bani Mostafa, Fadi Nayef; Abu- Mallouh, Riyad; Al-Hawawsheh, Sayel H (Research Journal in Advanced Humanities, 2026)
The study examines the impact of educational software on academic achievement and motivation among sixth-grade students in Jordan. The research included designing an educational program for space science and preparing an achievement test. A questionnaire was used to measure motivation. The study sample consisted of 140 male and female students from Elementary Schools. The results showed that there were statistically significant differences in pre- and post-achievement in favor of the experimental group. The study concluded with recommendations on the necessity of providing educational software for all educational levels and subjects, encouraging researchers to conduct more studies on computer use and preparing educational software, and encouraging science teachers to invest in educational software.